2017
DOI: 10.1038/s41598-017-13081-0
|View full text |Cite
|
Sign up to set email alerts
|

Anchorage of Au3+ into Modified Isoreticular Metal–Organic Framework-3 as a Heterogeneous Catalyst for the Synthesis of Propargylamines

Abstract: Postsynthetic modification of metal-organic framework is a general and practical approach to access MOF-based catalysts bearing multiple active sites. The isoreticular metal–organic framework-3 (IRMOF-3) was modified with lactic acid through condensation reaction of the carboxyl group of lactic acid and amino group present in IRMOF-3 frameworks. Au3+ was subsequently anchored onto the metal–organic framework IRMOF-3 using postsynthetic modification. The synthezized IRMOF-3-LA-Au (LA = lactic acid) was characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 67 publications
3
12
0
Order By: Relevance
“…For example, Liu et al sythesized an Au/MIL‐53(Al) catalyst‐containing Au 0 and Au 3+ species, which display good activity for the A 3 coupling reaction . In addition, Liu et al also demonstrated the Au 3+ ‐containing catalyst, IRMOF‐3‐LA‐Au, can exhibit good performance in the A 3 coupling reaction . Some comparative studies have been attempted, such as the contrastive properties of gold salts and Au 0 sponges, or the activity comparison between Au NPs/PMO (PMO = periodic mesoporous organosilica) and Au(PPh 3 )Cl .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Liu et al sythesized an Au/MIL‐53(Al) catalyst‐containing Au 0 and Au 3+ species, which display good activity for the A 3 coupling reaction . In addition, Liu et al also demonstrated the Au 3+ ‐containing catalyst, IRMOF‐3‐LA‐Au, can exhibit good performance in the A 3 coupling reaction . Some comparative studies have been attempted, such as the contrastive properties of gold salts and Au 0 sponges, or the activity comparison between Au NPs/PMO (PMO = periodic mesoporous organosilica) and Au(PPh 3 )Cl .…”
Section: Methodsmentioning
confidence: 99%
“…Compared with Au/MIL‐53(Al) catalyst fabricated via the impregnation method with HAuCl 4 , the hydroxyl and imine groups of MIL‐101‐SA can provide strong chelating/anchor sites to immobilize Au ions, rather than being adsorbed on the surfaces or pores of the MOF. Furthermore, in reference to IRMOF‐3‐LA‐Au (LA = lactic acid) catalyst, MIL‐101‐SA‐M exhibits much better water stability that allows the reaction to proceed in water and avoids the use of organic solvent. In a word, MIL‐101‐SA possesses excellent structural stability and chelating sites to stabilize Au species, making the resulting catalysts steadily catalyze the A 3 reaction in water.…”
Section: Methodsmentioning
confidence: 99%
“…To perform the A 3 coupling effectively, the selective and active catalysts are required. Numerous catalytic systems have been explored in the A 3 coupling till now [30][31][32][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. Among them copper, silver and gold catalysts seem to play the most vital role in promoting these transformations [30,32,[44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Among them copper, silver and gold catalysts seem to play the most vital role in promoting these transformations [30,32,[44][45][46]. Though the homogeneous version of A 3 couplings shows the high efficiency, the difficulties in catalyst reusability and product purification cause that, currently, the various heterogeneous catalysts, including immobilized metal complexes [30,34,47,48], coordination compounds [49,50] and nanocatalysts [30,32,[51][52][53][54][55] are examined intensively. The heterogeneous catalysts allow to limit polluting the final products with toxic metal species when the proper supports are selected.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that homogeneous catalysts suffer from the problem of catalyst separation and reuse, and also the problem of product contamination with generally toxic transition metals. Recently, a few heterogeneous and recyclable gold catalysts have been reported for A 3 coupling reactions . Along this line, recyclable gold nanoparticles (NPs) of 20 nm in size have been reported for the synthesis of propargylamines in CH 3 CN under efficient reaction conditions …”
Section: Introductionmentioning
confidence: 99%